1989
DOI: 10.1161/01.str.20.7.930
|View full text |Cite
|
Sign up to set email alerts
|

Regional cerebral blood flow and histopathologic changes after middle cerebral artery occlusion in rats.

Abstract: Changes in regional cerebral blood flow were correlated with the distribution of histopathologic signs of brain injury in 35 rats after middle cerebral artery occlusion. Rats were allowed to survive for periods of up to 4 weeks after the operation, and we focused particular interest on the time course of blood flow changes from the initial ischemic events to the late stage of infarction. Regional blood flow was measured using [ 14 C]iodoantipyrine and a quantitative autoradiographic technique. Blood flow in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(32 citation statements)
references
References 25 publications
3
29
0
Order By: Relevance
“…It is noteworthy that early hypoperfusion did recover except in the ipsilateral cortex. Consistent with the present data, a reduction in CBF in the striatum and periinfarct cortex has been shown by autoradiography at 7 days after permanent middle cerebral artery occlusion in rats (Bolander et al, 1989). This hypoperfusion resolved by 28 days after ischemia, which may be due to the establishment of collateral blood supply.…”
Section: Hypoperfusion At the Acute Phase In The Cortex And Thalamus supporting
confidence: 92%
“…It is noteworthy that early hypoperfusion did recover except in the ipsilateral cortex. Consistent with the present data, a reduction in CBF in the striatum and periinfarct cortex has been shown by autoradiography at 7 days after permanent middle cerebral artery occlusion in rats (Bolander et al, 1989). This hypoperfusion resolved by 28 days after ischemia, which may be due to the establishment of collateral blood supply.…”
Section: Hypoperfusion At the Acute Phase In The Cortex And Thalamus supporting
confidence: 92%
“…The change of LCGU values in the areas surrounding the ischemic center was gradual toward the caudal area, but sharp in the coronal plane. These results indicate that in an acute ischemic state, the degree of metabolic impairment is reflected by the blood supply, since the distribution and degree of LCGU reduction in the present study were similar to those of blood flow reduction in the acute state following MCA occlusion, as reported by Brint et al (21) and Bolander et al (22). We found that oxiracetam pretreatment for 3 days improved the impairment of glucose metabolism induced by focal ischemia.…”
Section: Physiological Variablessupporting
confidence: 92%
“…The neuron has classically been shown to be very sensitive to periods of cerebral ischemia. Flow reductions reaching 25ml/100g/minute in rodents are considered severe enough to lead to eventual cell death (Bolander et al, 1989). In addition to the severity of the ischemic insult, the duration of ischemia also determines vulnerability patterns (Heiss and Rosner, 1983).…”
Section: Cellular Vulnerabilitymentioning
confidence: 99%